Modernization of "transport" as a public transportation for pressing personal vehicle ownership in the city of Tanjung Pinang - Hari Dewi Purwasih; Raflis; Baginda Harahap (Journal of Intelligent Decision Support System (IDSS), 2023)
The Riau Archipelago, which consists of islands, has its own challenges in terms of development of infrastructure and transportation, so that development and growth each region is not the same, namely with 5 regencies and 2 municipalities. Island Riau includes having high potential in the field of tourism because every island Each has its own beauty and exoticism. Tanjung Pinang City as the Capital Provinces in the last decade have begun to develop and organize themselves into better in regional order but not yet in the transportation system. Public transport not yet felt as a very important thing because the people can still do it walk freely by using his private vehicle. But what is transport general public is still not a matter of urgency in the next decade?. This research is a descriptive research, descriptive research is one type research whose purpose is to provide a complete picture of social settings or intended for exploration and clarification of a phenomenon or social reality, by way of describing a number of variables relating to the problem and the unit studied among the phenomena tested. Here will be presented regarding the factual conditions existing transportation in Tanjung Pinang City and its relevance in the next decade.